2013
DOI: 10.1038/nature12082
|View full text |Cite
|
Sign up to set email alerts
|

Discrete clouds of neutral gas between the galaxies M31 and M33

Abstract: Spiral galaxies must acquire gas to maintain their observed level of star formation beyond the next few billion years. A source of this material may be the gas that resides between galaxies, but our understanding of the state and distribution of this gas is incomplete. Radio observations of the Local Group of galaxies have revealed hydrogen gas extending from the disk of the galaxy M31 at least halfway to M33. This feature has been interpreted to be the neutral component of a condensing intergalactic filament,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(95 citation statements)
references
References 25 publications
7
88
0
Order By: Relevance
“…They appear to emerge from M 31's HI disk. We also identified at these low radial velocities HI components positionally located close to the M 31/M 33 HI bridge at systemic velocities Wolfe et al 2013). Here, the confusion of M 31 HI gas with that of HVC complex H is most severe.…”
Section: Results and Comparison With Previous Studiesmentioning
confidence: 81%
See 1 more Smart Citation
“…They appear to emerge from M 31's HI disk. We also identified at these low radial velocities HI components positionally located close to the M 31/M 33 HI bridge at systemic velocities Wolfe et al 2013). Here, the confusion of M 31 HI gas with that of HVC complex H is most severe.…”
Section: Results and Comparison With Previous Studiesmentioning
confidence: 81%
“…To minimize systematic biases due to this Milky Way gas confusion, previous HI studies of M 31 and its environment either focused on structures at M 31's systemic velocities Wolfe et al 2013) around v LSR = −300 km s −1 or instead used upper radial velocity thresholds Westmeier et al 2005) ranging between −160 km s −1 ≤ v LSR ≤ −140 km s −1 . For the northern portion of the Leiden/Argentine/Bonn survey data (Kalberla et al 2005, LAB), the Leiden-Dwingeloo survey (Hartmann & Burton 1997, LDS), Blitz et al (1999) extended the analyzed radial velocity range up to v LSR ≤ −85 km s −1 and identified the "M 31 cloud" apparently connected in HI emission to M 31's disk.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent observations with the GBT at higher angular resolution showed that most of the emission was concentrated into discrete clouds (Wolfe et al, 2013(Wolfe et al, , 2016. Assuming that these clouds are at a distance of 800 kpc, between M31 and M33, they have M HI = 0.4 − 3.3 × 10 5 M , sizes of a few kpc, and are not associated with any stars or stellar stream.…”
Section: M31-m33 Cloudsmentioning
confidence: 99%
“…gas in the outskirts of the disc (Koch et al 2015;Lehner et al 2015;Wolfe et al 2013;Lockman et al 2012) is ruled out. No high velocity clouds have been detected in CO (Combes & Charmandaris 2000;Miville-Deschênes et al 2005), while Galactic gas should be around 0 km s −1 .…”
Section: Different Velocity Componentsmentioning
confidence: 99%